Synthesis of Semi-Synthetic Chalcones from the Isolated Intermediate Aldehydes of the Roots of Decalepis hemiltonii - JAYACHANDRA REDDY, B.; SATISH REDDY, K.; PARTHASARATHY, T. (Asian Journal of Chemistry, 2010)
Chalcones, 4-hydroxy-3-(3-(4-methoxy-phenyl)-acryloyl) benzoic acid (a1), 3-(3-(4-ethoxy-phenyl)-acryloyl)-4-hydroxy-benzoic acid (b1) were prepared by an aldol condensation between 3-acetyl-4-hydroxy benzoic acid (iv) and isolated aromatic aldehydes from tuberous roots of Decalepis hemiltonii in the presence of potassium hydroxide as a base. Flavone, 2-(4-ethoxy-phenyl)-4-oxo-4H-chromene-6-carboxylic acid (c1) prepared from chalcone (b1) through cyclization via bromination. The aromatic aldehydes, anisaldehyde (a), salicylaldehyde (b), vanillin (c), 2-hydroxy-4-methoxy benzaldehyde (d), isovanillin (e), p-ethoxy benzaldehyde (f) and benzaldehyde (g) were isolated from the tuberous roots of Decalepis hemiltonii. The structures of compounds i-iv, a-g, a1-c1 were elucidated on the basis of spectral and chemical studies.